The productive use of free time : the utilisation of deterministic maintenance opportunity windows due to excess capacity in large coupled production lines with finite buffers - Durandt, Casper (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.